143-3x=33x+15

Simple and best practice solution for 143-3x=33x+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 143-3x=33x+15 equation:


Simplifying
143 + -3x = 33x + 15

Reorder the terms:
143 + -3x = 15 + 33x

Solving
143 + -3x = 15 + 33x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-33x' to each side of the equation.
143 + -3x + -33x = 15 + 33x + -33x

Combine like terms: -3x + -33x = -36x
143 + -36x = 15 + 33x + -33x

Combine like terms: 33x + -33x = 0
143 + -36x = 15 + 0
143 + -36x = 15

Add '-143' to each side of the equation.
143 + -143 + -36x = 15 + -143

Combine like terms: 143 + -143 = 0
0 + -36x = 15 + -143
-36x = 15 + -143

Combine like terms: 15 + -143 = -128
-36x = -128

Divide each side by '-36'.
x = 3.555555556

Simplifying
x = 3.555555556

See similar equations:

| 2x-x^3+5=0 | | 5p+p-4p= | | x*x+x=420 | | X^2-5X-23=0 | | 3-3p=4-2p | | 6x^2-2x=-x+6x^2 | | 14g= | | 107-6x=12x-21 | | 375.6m= | | x^5-x+3=0 | | 97-3x=7-8x | | 2x+1=+5 | | 2x^2-6x+2x-6=0 | | 1,5=0,15 | | -6u-5=13 | | x^2+27x-28=0 | | (x+1)(2x-6)=0 | | 23s+45=19s-39 | | 7t-17=6t+16 | | 12x-4=7x+14 | | 5x+9=2x+36 | | 4-6x=6x+10 | | 4x-25=7 | | 2(a-5)+4(a-5)= | | x+5,4-2x+1.8=1,2(2-x) | | 9x-6=15+2x | | 3(x-2)=2(4x+1)-3 | | 5x+2x^2=0 | | 12x+3-4x=8x+2-3x | | ln(x)-ln(4)=11 | | X^2+10X-3200=0 | | X^2+10X-800=0 |

Equations solver categories